Precise evaluation of the postoperative cochlear duct length by flat-panel volume computed tomography – Application of secondary reconstructions. (2nd January 2022) - Schendzielorz, Philipp; Ilgen, Lukas; Müller-Graff, Franz-Tassilo; Noyalet, Laurent; Völker, Johannes; Taeger, Johannes; Hagen, Rudolf; Neun, Tilmann; Zabler, Simon; Althoff, Daniel; Rak, Kristen
Abstract : Objective: There is still a lack in precise postoperative evaluation of the cochlea because of strong artifacts. This study aimed to improve accuracy of postoperative two-turn (2TL) and cochlear duct length (CDL) measurements by applying flat-panel volume computed tomography (fpVCT), secondary reconstruction (fpVCTSECO ) and three-dimensional curved multiplanar reconstruction. Methods: First, 10 temporal bone specimens with or without electrode were measured in multi-slice computed tomography (MSCT), fpVCT and fpVCTSECO and compared to high-resolution micro-CT scans. Later, pre- and postoperative scans of 10 patients were analyzed in a clinical setting. Results: Concerning 2TL, no statistically significant difference was observed between implanted fpVCTSECO and nonimplanted micro-CT in 10 temporal bone specimens. In contrast, there was a significant discrepancy for CDL (difference: −0.7 mm, P = 0.004). Nevertheless, there were no clinically unacceptable errors (±1.5 mm). These results could be confirmed in a clinical setting. Using fpVCTSECO, CDL was slightly underestimated postoperatively (difference: −0.5 mm, P = 0.002) but without any clinically unacceptable errors. Conclusion: fpVCTSECO can be successfully applied for a precise measurement of the cochlear lengths pre- and postoperatively. However, users must be aware of a slight systematic underestimation of CDL postoperatively. These results may help to refine electrode selection and frequency mapping.